Use of Religious Counseling (Islami) to Improve Psychological Well Being on Students of SMK Nusantara Wisata Respati Jakarta - Devi Ratnasari; Miskanik Miskanik; Ayu Rahmaniah (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
This study aims to determine the effectiveness of religious counseling services on improving psychological well-being in students of SMK Nusantara Wisata Respati Jakarta. The research method used is quantitative research with quasi experimental type, and using purposive sampling technique in sampling. The subjects of the study were the students of grade XII of SMK Nusantara Wisata Respati who had low score in psychological well-being as many as 6 people. The instrument used is the psychological well-being scale developed by Ryff. Based on result of data analysis by using sign test, known r = 0,009, so it can be concluded that the use of effective religious counseling can improve psychological well-being on the students of class XII SMK Nusantara Wisata Respati Jakarta. This proves that religious counseling services are very useful in improving students' psychological well-being. Increased psychological well-being is expected to optimize student achievement so that its potential can be used optimally